Thermal stability of corncob charcoal produced by microwaves - Santos, Carolina M.; Oliveira, Leandro S. de; França, Adriana S. (Revista Hipótese, 2018)
The aim of this work was to characterize the thermal degradation of charcoals produced by microwave treatment of corncobs. Thermogravimetric analysis allowed the identification of three phases of material decomposition, with this characteristic being also observed for the charcoals. It was observed that there was a significant difference in the preparation time between the different granulometries; however, when compared to the time necessary for carbonization in a muffle oven, such diferences were negligible. The thermal stability of the charcoals of different granulometries did not show significant diferences, with the produced charcoals presenting final yields in the range of 20 to 25%.
Keywords: Corncob; Coal; Microwave